The study on the aspect ratio of Atomic Force Microscope (AFM) measurements for Triangular Silicon Nanowire - Za'bah, Nor Farahidah; Kwa, Kelvin S. K.; O'Neill, Anthony (2013)
A top-down silicon nanowire fabrication using a combination of optical lithography and orientation dependent etching (ODE) has been developed using <100> Silicon-on Insulator (SOI) as the starting substrate. The use of ODE etchant such as potassium hydroxide (KOH) and Tetra-Methyl Ammonium Hydroxide (TMAH) is known to create geometrical structures due to its anisotropic mechanism of etching. In this process flow, using the <100> SOI substrate, a triangular shape silicon nanowire is successfully fabricated. The triangle silicon nanowire has <111> planes on each side which theoretically produces an angle of 54.7 with the <100> horizontal plane. One of the geometrical characterizing methods that were used to confirm the fabrication of the silicon nanowire is by using Atomic Force Microscope (AFM). In this paper, the study on the aspect ratio of the AFM measurements is presented. This experimental study would demonstrate the importance of having a high aspect ratio cantilever when a nanowire with a thickness of less than 200 nm is concerned